“Diseño de un plan estratégico de marketing para la empresa Fix Equipment S. A en el distrito metropolitano de Quito” - Mejía Parra, Martha Susana (2013)
The aim of this present work is develop basic marketing concepts through the design of a strategic marketing plan for the company Fix Equipment S.A. which is responsible for developing technological solutions. At the beginning, this work describes the current theoretical foundation of marketing. After that, the business philosophy is made up to describe the strategic direction of the company, and then the analysis of the marketing is focused on understanding macro, micro and internal environment identifying strengths, opportunities, threats and weaknesses of the company.